Effects of lethal management on gray wolf pack persistence and reproduction in Wisconsin, USA - Alejandra Zubiria Perez; Kenneth F. Kellner; David M. MacFarland; Jennifer L. Price Tack; David B. Ruid; Glenn E. Stauffer; Jerrold L. Belant (Scientific Reports, 2024)
Abstract Direct human-caused mortality accounts for about half of all large mammal mortality in North America. For social species like gray wolves (Canis lupus), the death of pack members can disrupt pack structure and cause pack dissolution, and mortality of breeding adults or wolves during reproduction and pup-rearing can decrease pup recruitment. We estimated minimum and maximum probability of wolf pack persistence in Wisconsin, USA, during biological years (15 April–14 April) 2011–2019 and evaluated the influence of pack size and legal harvest mortality on pack persistence during 2012–2014. Harvests comprised 75–161 mortalities within 194 monitored packs during 2012–2014, with 56–74% of packs having no wolves harvested each year. As an index of reproduction during 2013–2019, we also estimated the proportion of packs where pups responded to howl surveys. We evaluated the influence of pack size, legal harvest, and agency removal on reproduction during 2013–2015. Annual maximum pack persistence probability was uniformly high (0.95–1.00), and annual minimum pack persistence probability ranged from 0.86–0.98 with a possible decline during years of harvest. Reproduction was similar in years following harvest and agency removal (2013–2015, pup response = 0.27–0.40), and years without harvest or agency removal the year prior (2016–2019, pup response = 0.28–0.66). Pack size had a positive effect on pack persistence and reproduction. Total number of wolf mortalities and number of adult male and females removed did not influence pack persistence or reproduction. We suggest that low per-pack mortality, timing of harvest and agency removal, and harvest characteristics during 2012–2014 supported stable pack persistence and reproduction.